2021
DOI: 10.1089/fpd.2021.0005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Shiga Toxin–Producing Escherichia coli from Retail Beef Samples from Eight Provinces in China

Abstract: While Shiga toxin-producing Escherichia coli (STEC) is a major foodborne pathogen worldwide, data on the molecular and phylogenetic properties of STEC isolates from retail beef samples in China remain scant. Fresh retail beef samples (n = 1062) were collected from eight provinces, and STEC isolates were recovered and characterized. PCR data showed that more than 50% of the samples were stx positive, and 82 STEC isolates were recovered from 14.8% (79/535) stx-positive enriched broths. In contrast, all ciproflox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Strains of E. coli that produce STEC are the reason for an array of infections in people and animals, encompassing gastrointestinal and extra-intestinal difficulties like urinary tract infections. ( Bentancor et al, 2007 , Hu et al, 2021 , Pan et al, 2021 ). Extra-intestinal pathogenic E. coli ’s (ExPEC) involvement in causing severe infections has recently attracted attention regarding its zoonosis from a veterinary clinical standpoint ( Bélanger et al, 2011 , Pitout, 2012 , Najafi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strains of E. coli that produce STEC are the reason for an array of infections in people and animals, encompassing gastrointestinal and extra-intestinal difficulties like urinary tract infections. ( Bentancor et al, 2007 , Hu et al, 2021 , Pan et al, 2021 ). Extra-intestinal pathogenic E. coli ’s (ExPEC) involvement in causing severe infections has recently attracted attention regarding its zoonosis from a veterinary clinical standpoint ( Bélanger et al, 2011 , Pitout, 2012 , Najafi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, various studies have shown STEC contaminations in raw meats ( Bai et al, 2015 ; Chao et al, 2007 ; Dong et al, 2020 ; Li et al, 2011 ; Zhou et al, 2002 ). Of note, a recent study reported multidrug resistant STEC strains with high pathogenic potential from retail beef in China ( Hu et al, 2021 ), this knowledge is limited for mutton-derived strains. The objective of this study was to depict the prevalence, genomic and antimicrobial characteristics of STEC strains in retail raw meats with a particular interest on mutton in Jinan, Shandong, China, and to assess their pathogenic potential.…”
Section: Introductionmentioning
confidence: 99%